Effects of a single power strength training session on heart rate variability when performed at different simulated altitudes - Alvarez-Herms, J.; Julià-Sánchez, S.; Gatterer, H.; Corbi, F.; Viscor, G.; Burtscher, M. (High Altitude Medicine & Biology, 2020)
Background: This study assessed heart rate variability (HRV) after a single power strength training session performed at different hypoxic levels.